Pengembangan Proses pada Sistem Anaerobic Baffled Reactor untuk Memenuhi Bakumutu Air Limbah Domestik - Elis Hastuti; Reni Nuraeni; Sri Darwati (Jurnal Permukiman, 2017)
The wastewater treatment  infrastructure had provided by the government mainly through  application of communal wastewater treatment plant (WWTP).  The  treatment process  of communal WWTP  applied  generally  anaerobic system, such as Anaerobic Baffled Reactor (ABR) technology, but most of  treated water  do not meet effluent standard. This paper aims to research the characteristics of the organic removal and treatment upgrading process in the communal ABR system, including process modification or combination with other system. Research carried out in several communal WWTP  has applied since the year 2012-2013 in Cimahi City, West Java. Method of evaluation was conducted in the WWTP management through observation of  serviced community, operation and maintenance,  water quality test both physically and chemicaly. Method of qualitative descriptive  for analysis factors affecting the process performance of ABR and  potential process upgrading of  ABR system according to characteristic of ABR system. The organic removal in ABR system  is influenced by the management, existence of pra treatment unit,  acclimatization process, water consumption and environment of serviced area. Upgrading process of ABR system  can be performed by modification of baffle design, start-up process, maintenance biomass,  hybrid system, recirculation systems and application of  further treatment. The   review these alternative of ABR upgrading process are important in the ABR planning standard  to achieve   treated water  meet effluent standard.